2020
DOI: 10.1155/2020/1480281
|View full text |Cite
|
Sign up to set email alerts
|

Perivascular Lymphocyte Clusters Induced by Gastric Subserous Layer Vaccination Mediate Optimal Immunity against Helicobacter through Facilitating Immune Cell Infiltration and Local Antibody Response

Abstract: Background. In situ vaccination-induced local inflammatory response resulted in the establishment of a pool of tissue-resident memory T (TRM) cells and new vessels after the resolution of inflammation. TRM cells have received increasing attention; however, the role of new vessels in protective response is still unknown. Materials and Methods. We performed the laparotomy to access the stomach and injected alum-based vaccine into the gastric subserous layer (GSL). At 28 days post vaccination, a parabiosis mouse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Primary and secondary lymphoid follicles have also been described in healthy human gastric mucosae (41) and the mucosae and submucosae of healthy piglets (42). Recently, it was shown that subserous delivery of an H. pylori vaccine to the murine stomach wall (via surgical laparotomy) generated new perivascular lymphocyte clusters and CD4 + tissue resident memory T cells (11,43,44), further confirming inductive potential. Moreover, our group has developed an ingestible selforienting device that can inject a dose of biologic directly into the gastric wall (20).…”
Section: Stomachmentioning
confidence: 83%
“…Primary and secondary lymphoid follicles have also been described in healthy human gastric mucosae (41) and the mucosae and submucosae of healthy piglets (42). Recently, it was shown that subserous delivery of an H. pylori vaccine to the murine stomach wall (via surgical laparotomy) generated new perivascular lymphocyte clusters and CD4 + tissue resident memory T cells (11,43,44), further confirming inductive potential. Moreover, our group has developed an ingestible selforienting device that can inject a dose of biologic directly into the gastric wall (20).…”
Section: Stomachmentioning
confidence: 83%